2020
DOI: 10.1002/er.5153
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis of MoS 2 QDs/TiO 2 nanosheets via a self‐assembly strategy for enhanced photocatalytic hydrogen production

Abstract: Summary The MoS2 quantum dots (QDs) were interspersed on anatase TiO2 nanosheets with exposed (001) facets by a facile self‐assembly strategy. As expected, the MoS2 QDs/TiO2 nanosheets display an excellent photocatalytic performance for hydrogen production, and its hydrogen evolution rate is 139 μmol/h/g. More importantly, the hydrogen evolution rate of MoS2 QDs/TiO2 nanosheets is almost 4‐fold in comparison to that of nude TiO2 nanosheets. Based on the detailed characterizations, it can be obtained that the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 48 publications
(93 reference statements)
1
16
0
Order By: Relevance
“…The distinct lattice fringes with a distance of about 0.35 nm can be observed, which is assigned to the (101) crystal plane of anatase TiO 2 . 4 In addition, the lattice fringes of d-spacings of about 0.23 nm can be obtained, which is consistent with the (111) crystal plane of CuO. 24 Fig.…”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…The distinct lattice fringes with a distance of about 0.35 nm can be observed, which is assigned to the (101) crystal plane of anatase TiO 2 . 4 In addition, the lattice fringes of d-spacings of about 0.23 nm can be obtained, which is consistent with the (111) crystal plane of CuO. 24 Fig.…”
Section: Resultssupporting
confidence: 78%
“…It can be concluded that the two peaks at 458.6 eV and 464.3 eV are assigned to Ti 2p 3/2 and Ti 2p 1/2 of Ti 4+ in TiO 2 , respectively. 4 Similarly, the binding energy of the O 1s peak at 529.9 eV can be assigned to lattice oxygen, and the other peak at 530.6 eV is identified with surface hydroxyls in CuO/TiO 2 . 36 Importantly, there are two peaks located at approximately 932.5 eV and 952.1 eV, corresponding to Cu 2p 3/2 and Cu 2p 1/2 , respectively.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The doping and sensitization strategies can obviously intensify the light adsorption efficiency to improve the photocatalytic performance 23,24 . Furthermore, some fabricating heterostructures with a suitable band gap semiconductor or metals can heighten efficiency of the photo‐excited carriers' separation and migration 25‐27 . Therefore, if a suitable metal or semiconductor photocatalyst is chosen as cocatalyst, this strategy does not merely enhance separation and transfer of photo‐excited charge carriers, but also improve utilization ratio of photo‐generated electrons and holes on the surface of composite semiconductor photocatalyst.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10] For instance, harvesting hydrogen gas as a clean energy source through photocatalytic water splitting is one of the most promising strategies. [11][12][13][14][15][16][17][18] Inspired by Fujishima and Honda's first discovery of photoelectrochemical water splitting on a TiO 2 photoanode, 19 significant efforts have been devoted to taking TiO 2 -based photocatalysts to the next level, owing to their low cost and remarkable stability. [20][21][22][23][24][25][26] With proven catalytic activity, TiO 2 is the model material in photocatalysis and photoelectrochemistry.…”
mentioning
confidence: 99%